Hubungan Online Disinhibition Effect Dengan Kecenderungan Perilaku Cyberbullying Pada Siswa MA Pengguna Instagram - Dearnie Regina Lestari; M Ahkam Alwi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The high level of internet use, social media, and the online disinhibition effect trigger the emergence of the phenomenon of cyberbullying in students. The impact of cyberbullying is not only felt by the victim, but also the perpetrator of cyberbullying who may experience long-term implications such as decreased self-esteem, increased antisocial attitudes, and violence or criminal behavior in adulthood. This study aims to determine the relationship between online disinhibition effect and the tendency of cyberbullying behavior in MA students who use Instagram. This study uses quantitative research methods with research respondents totaling 90 MA students. The sampling method in this study was purposive sampling. The measuring instruments used are the online disinhibition effect scale and the cyberbullying scale. The data from this study were analyzed using the Spearman's rho correlation test with the help of SPSS version 26 for windows. The results showed that there is a very significant positive relationship between the online disinhibition effect and the tendency of cyberbullying behavior in MA students who use Instagram with a correlation value of 0.519 and a significance value of 0.000. This means that the higher the online disinhibition effect, the higher the tendency of cyberbullying behavior. The implication in this study is to provide information and an overview of the relationship between the online disinhibition effect and the tendency of cyberbullying behavior in MA students who use Instagram to become the basis for self-evaluation in social media, so that healthier relationships and communication can be established and cyberbullying does not occur.